Differing roles for members of the phospholipase A2 superfamily in experimental autoimmune encephalomyelitis - Kalyvas, Athena; Baskakis, Constantinos; Magrioti, Victoria; Constantinou-Kokotou, Violetta; Stephens, Daren; López-Vales, Rubèn; Lu, Jian-Qiang; Yong, V. Wee; Dennis, Edward A.; Kokotos, George; David, Samuel (Brain, 2009)
The phospholipase A2 (PLA2) superfamily hydrolyzes phospholipids to release free fatty acids and lysophospholipids, some of which can mediate inflammation and demyelination, hallmarks of the CNS autoimmune disease multiple sclerosis. The expression of two of the intracellular PLA2s (cPLA2 GIVA and iPLA2 GVIA) and two of the secreted PLA2s (sPLA2 GIIA and sPLA2 GV) are increased in different stages of experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis. We show using small molecule inhibitors, that cPLA2 GIVA plays a role in the onset, and iPLA2 GVIA in the onset and progression of EAE. We also show a potential role for sPLA2 in the later remission phase. These studies demonstrate that selective inhibition of iPLA2 can ameliorate disease progression when treatment is started before or after the onset of symptoms. The effects of these inhibitors on lesion burden, chemokine and cytokine expression as well as on the lipid profile provide insights into their potential modes of action. iPLA2 is also expressed by macrophages and other immune cells in multiple sclerosis lesions. Our results therefore suggest that iPLA2 might be an excellent target to block for the treatment of CNS autoimmune diseases, such as multiple sclerosis.